Klasifikasi Citra Dalam Identifikasi Jeruk Nipis dan Jeruk Mandarin Menggunakan Convolutional Neural Network (CNN) Dan Optimalisasi Median Filter - Erlanda, Hadrian; Saputra, Randy; Ramadhanu, Agung (LPPM STIKOM Tunas Bangsa, 2025)
With the rapid advancement of technology in the field of image processing, farmers are increasingly supported in identifying types of citrus fruits. This study aims to differentiate between lime (Citrus aurantiifolia) and mandarin orange (Citrus reticulata) using image processing methods and morphological analysis. Image processing is employed to examine visual differences based on factors such as color, texture, and size of the fruit. Additionally, chemical analysis is conducted to distinguish the composition of compounds found in both types of citrus. The results of the study show that this approach is effective in identifying the differences between lime and mandarin orange with high accuracy, and can be applied in various industries, including agriculture and food processing